2020
DOI: 10.1371/journal.pmed.1003053
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre and whole grains in diabetes management: Systematic review and meta-analyses

Abstract: Background Fibre is promoted as part of a healthy dietary pattern and in diabetes management. We have considered the role of high-fibre diets on mortality and increasing fibre intake on glycaemic control and other cardiometabolic risk factors of adults with prediabetes or diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
173
2
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(229 citation statements)
references
References 79 publications
5
173
2
14
Order By: Relevance
“…In a separate study from Mexico on 217 adolescents, it was demonstrated that those with the highest dietary fibre intake had lower odds of homeostasis model assessment of insulin resistance (HOMA-IR) >2.97 (OR 0.34; 95% CI 0.13–0.93), following adjustments for age, sex, body fat percentage and intake of saturated fatty acids [ 38 ]. Finally, in a recent systematic review and meta-analysis on the effects of dietary fibre and whole grains in the management of Diabetes Mellitus, there was an association of high-fibre diet with improved insulin sensitivity, including many other aspects of metabolic health, such as HbA1C, lipid profile, body weight and C-reactive protein [ 39 ]. There is, however, a deficiency of published longer-term controlled studies (>12 months) on the metabolic effects of increasing dietary fibre intake [ 39 ] (with a notable exception [ 35 ]), and this should be a focus for future research in this field.…”
Section: The Benefits Of Dietary Fibrementioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study from Mexico on 217 adolescents, it was demonstrated that those with the highest dietary fibre intake had lower odds of homeostasis model assessment of insulin resistance (HOMA-IR) >2.97 (OR 0.34; 95% CI 0.13–0.93), following adjustments for age, sex, body fat percentage and intake of saturated fatty acids [ 38 ]. Finally, in a recent systematic review and meta-analysis on the effects of dietary fibre and whole grains in the management of Diabetes Mellitus, there was an association of high-fibre diet with improved insulin sensitivity, including many other aspects of metabolic health, such as HbA1C, lipid profile, body weight and C-reactive protein [ 39 ]. There is, however, a deficiency of published longer-term controlled studies (>12 months) on the metabolic effects of increasing dietary fibre intake [ 39 ] (with a notable exception [ 35 ]), and this should be a focus for future research in this field.…”
Section: The Benefits Of Dietary Fibrementioning
confidence: 99%
“…Finally, in a recent systematic review and meta-analysis on the effects of dietary fibre and whole grains in the management of Diabetes Mellitus, there was an association of high-fibre diet with improved insulin sensitivity, including many other aspects of metabolic health, such as HbA1C, lipid profile, body weight and C-reactive protein [ 39 ]. There is, however, a deficiency of published longer-term controlled studies (>12 months) on the metabolic effects of increasing dietary fibre intake [ 39 ] (with a notable exception [ 35 ]), and this should be a focus for future research in this field.…”
Section: The Benefits Of Dietary Fibrementioning
confidence: 99%
“…Dietary fibre from cereals was found to be effective in reducing the postprandial blood glucose response (i.e., blood glucose levels after a meal) and increasing the insulin response [ 113 ]. As outlined above, soluble dietary fibre has the capacity to increase the viscosity of stomach content.…”
Section: Dietary Fibre From Whole Grains and Health Implicationsmentioning
confidence: 99%
“…Wheat-based foods have been staple foods since wheat was domesticated about 10,000 years ago, and they constitute a major source of macro-and micronutrients and energy (15-20% of the required intake) for the world population, especially in developing countries (2,3). Many health benefits such as favorable weight management and reductions in the risks for cardiovascular diseases and type 2 diabetes have been shown to be associated with the consumption of wheat-based foods, especially made of whole grains (4)(5)(6). Moreover, many non-food products for daily use contain wheat constituents as valuable ingredients.…”
Section: Introductionmentioning
confidence: 99%